Pengaruh Program Gemar Makan Ikan “Germarikan” Terhadap Minat Konsumsi Ikan Masyarakat (Studi Kasus Dusun Karanganom, Wonokromo, Pleret, Kabupaten Bantul) - Andrianto, N. Marantika; Prasetiyowati, Sri Haryanti (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2020)
In 2017, the level of fish consumption in Special Region of Yogyakarta (DIY) reached 23,75 kg/capita, this has not yet reached the national average set of 47 kg/capita. The government is trying to increase the level of consumption through a program brought by them named GEMARIKAN program. The objectives of the research are 1) determine the knowledge level of housewives in Karanganom Village about Gemarikan program 2) know the influence of Gemarikan Program in boosting the interest in fish consumption by Karanganom Village society. The research was conducted in the months of September to December 2019. The researcher has taken 36 housewives as the sample of the research by using purposive sample taking technique. Data collecting technique used by the researcher are interview, questionnaire, and food frequency. Data processing used in testing the questionnaire validity and the level of confidence are a test of validity and reliability. Analysis of the data used validatases and reliability tests using SPSS software. The result of the research shows that the level of the Gemarikan program influence toward consumption interest of Karanganom Village society has a value of 1.9% and the remaining 89.1 influenced by another factors. The Research conclude that knowledge is the housewives have shown are quite good. The influence of the Gemarikan program toward Karanganom village society is very good.